Character of abdominal surgery for polycystic kidney in animals and the role of indicators of sonographic examination at different stages of surgical intervention - Dekhnych, I. (Scientific Progress & Innovations, 2023)
The article is devoted to the study of the role of sonography at various stages of abdominal surgery for polycystic kidney disease in animals and contains a description of the technique of sonography during surgery. The article examines the peculiarities of animal preparation for surgery, the operation itself, and the postoperative period from the point of view of the use of sonography. All these phases are described in detail in the article, taking into account all the necessary conditions, factors and recommendations. The impact of sonography on reducing the duration of surgery, improving the quality of cyst removal and reducing the risk of complications was analyzed. Based on the works of scientists, it is described that the use of sonography at various stages of surgical intervention for polycystic kidneys can significantly improve the quality of the operation and reduce its time. Special techniques of sonography in abdominal surgery, such as dopplerography, color dopplerography, 3D and 4D sonography, elastography, intraoperative and intraperitoneal sonography, duplex scanning of renal arteries and veins, are considered. Various methods of cyst treatment have been described, including extraction (removal), drainage, resection (partial removal), nephrectomy (complete removal). The types of instruments used to remove cysts are described, including: endograbbler, endoclipper, endobur, endoscope, laparoscope. Disadvantages of the use of sonography are considered, which force veterinarians to combine sonography with other diagnostic methods, such as radiography, computer tomography, magnetic resonance imaging, and others, in order to obtain maximum information about the state of the animal’s kidneys and determine the optimal treatment plan. The article provides an overview of scientific research on this topic and emphasizes that abdominal surgery for polycystic kidney disease in animals can be performed using different methods depending on the size and number of cysts in the kidneys. The information provided in the article may be useful for veterinarians who treat animals with polycystic kidney disease.